2018
DOI: 10.1111/cen.13753
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and surgical treatment of nonreproductive outcomes in polycystic ovary syndrome: An overview of systematic reviews

Abstract: There is reliable evidence regarding the use of metformin for anthropometric outcomes and COCPs for hyperandrogenism in women with PCOS but not for other interventions. There is significant gap in knowledge regarding the management of psychological outcomes in women with PCOS which needs further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 78 publications
(577 reference statements)
0
19
0
6
Order By: Relevance
“…53 Previous studies have raised concerns of COCPs affecting insulin resistance and triglycerides; however, a recent overview of systematic reviews found no evidence of increased cardiovascular events in prolonged use of COCPs. 54 There is limited information on which COCP preparation type or duration of therapy is optimal for women with PCOS, with all agents reducing SHBG and improving clinical outcomes. Therefore, to minimize complications and based on general population data, recommendations are to use the lowest effective estrogen dose and natural estrogen preparations, balancing efficacy, metabolic risk profile, side effects, costs, and availability.…”
Section: Treatment Of Nonreproductive Outcomesmentioning
confidence: 99%
“…53 Previous studies have raised concerns of COCPs affecting insulin resistance and triglycerides; however, a recent overview of systematic reviews found no evidence of increased cardiovascular events in prolonged use of COCPs. 54 There is limited information on which COCP preparation type or duration of therapy is optimal for women with PCOS, with all agents reducing SHBG and improving clinical outcomes. Therefore, to minimize complications and based on general population data, recommendations are to use the lowest effective estrogen dose and natural estrogen preparations, balancing efficacy, metabolic risk profile, side effects, costs, and availability.…”
Section: Treatment Of Nonreproductive Outcomesmentioning
confidence: 99%
“…However, in order to reduce the thromboembolic risk, the lowest effective estrogen doses (such as 20–30 μg of ethinylestradiol) or the use of natural estradiol should be preferred. Even though clinical trials ( 127 ) almost always use COCPs containing antiandrogen progestins (due to higher effect on hyperandrogenism symptoms), the guidelines do not recommend a specific progestin. A recent meta-analysis showed that COCPs containing cyproterone acetate are more effective in suppressing gonadotropins, leading to a decrease in androgen levels ( 128 ).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the population was women with PCOS, and the intervention was a systematic review with or without a meta-analysis with a primary focus on genetic associations. Systematic reviews not on the genetics of PCOS (e.g., focusing on assessment or treatment) were excluded and are the focus of separate OSRs [28,29]. The specific inclusion criteria for systematic reviews were a publication date from 2009 onwards, description of a search strategy containing at least key words or terms, inclusion of the number of identified and included articles, and quality appraisal of the articles.…”
Section: Methodsmentioning
confidence: 99%